Isolation and Identification of Eurotium cristatum from Different Dark Tea Sources and the Effect of Solid-state Fermentation on the Nutritional and Functional Components of Tartary Buckwheat - Shuqi LIU; Haonan ZHENG; Yuan XIN; Chen XIA; Jianglin ZHAO; Xiaoqin ZHENG; Liang ZOU; Dabing XIANG; Liangzhen JIANG (Shipin gongye ke-ji)
Candidate Eurotium cristatum strains from 8 types of commercial dark tea were isolated and identified. Solid-state fermentation of tartary buckwheat grains by isolated Eurotium cristatum strains was carried out. The content of nutrients, including total starch, soluble proteins, fats, and reducing sugars, and functional components flavonoids and polyphenols before and after fermentation, was measured. The transformation effects of different Eurotium cristatum strains on the nutritional and functional components of tartary buckwheat were compared. Moreover, the activities of two rate-limiting enzymes (phenylalanine ammonia lyase and polyphenol oxidase), responsible for the biosynthesis of key buckwheat pharmaceutical components flavonoids and polyphenols, were determined. Results showed that, among the 8 candidate strains, 7 strains were identified as Eurotium cristatum, with the other strain being Aspergillus chevalieri. The content of total starch, soluble proteins, and fats in the fermentation system after fermentation were significantly lower than those before fermentation (P<0.05), while most of the content of reducing sugars, and functional components including total flavonoids and total polyphenols, was significantly higher than before fermentation (P<0.05). The fermentation products with LB and YZ strains had relatively higher total flavonoid content, while those with JW and YZ strains had relatively higher total polyphenol content. Correlation analysis showed that the content of total flavonoids and polyphenols in fermented tartary buckwheat were significantly positively correlated with the activities of phenylalanine ammonia lyase and polyphenol oxidase (P<0.001), respectively, while the contents of reducing sugars were significantly negatively correlated with total starch (P<0.001). These resultsed suggest that the changes in nutritional and functional components in the fermented tartary buckwheat were closely related to the biotransformation by Eurotium cristatum. This study can provide a theoretical basis for the development of new fermented tartary buckwheat products.